2021
DOI: 10.1007/s00401-020-02248-1
|View full text |Cite
|
Sign up to set email alerts
|

The mechanistic link between selective vulnerability of the locus coeruleus and neurodegeneration in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is neuropathologically characterized by the intracellular accumulation of hyperphosphorylated tau and the extracellular deposition of amyloid-β plaques, which affect certain brain regions in a progressive manner. The locus coeruleus (LC), a small nucleus in the pons of the brainstem, is widely recognized as one of the earliest sites of neurofibrillary tangle formation in AD. Patients with AD exhibit significant neuronal loss in the LC, resulting in a marked reduction of its size and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 178 publications
(312 reference statements)
1
85
0
Order By: Relevance
“…This process might be influenced by manifold variables, such as ageing, the degree of biological brain maintenance and even dementia progression, which is likely to exacerbate this “caudal-shifting” process. Moreover, it is acknowledged how the noradrenergic system is susceptible to compensatory changes across the brain involving the caudal portion of the LC and peri-coeruleus/LC-peri-dendritic regions (Epi-coeruleus and Sub-coeruleus) [ 14 , 54 , 55 , 61 , 103 , 104 , 105 , 106 ]. Therefore, a larger area rather than a very specific and concise region would be more informative and appropriate while investigating the LC–NA system on different groups, particularly known the heterogeneity of Alzheimer’s disease.…”
Section: Methodsmentioning
confidence: 99%
“…This process might be influenced by manifold variables, such as ageing, the degree of biological brain maintenance and even dementia progression, which is likely to exacerbate this “caudal-shifting” process. Moreover, it is acknowledged how the noradrenergic system is susceptible to compensatory changes across the brain involving the caudal portion of the LC and peri-coeruleus/LC-peri-dendritic regions (Epi-coeruleus and Sub-coeruleus) [ 14 , 54 , 55 , 61 , 103 , 104 , 105 , 106 ]. Therefore, a larger area rather than a very specific and concise region would be more informative and appropriate while investigating the LC–NA system on different groups, particularly known the heterogeneity of Alzheimer’s disease.…”
Section: Methodsmentioning
confidence: 99%
“…The LC has been shown to exhibit early signs of neurodegeneration before the DR nucleus [31], and patients with dementia exhibit significantly reduced Noradrenaline transporters (NET) in the LC but not in the DR [128]. Together these findings suggest that noradrenergic neurons within the DR might provide compensatory support for the broader LC-NA system [128,106,178,180]. Accordingly, the resilience of the DR as a compensatory nucleus to the LC-NA system decay may, in part, explain the observed relationships between DR volume and BrainPAD in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, although the LC shows markers of neurodegeneration years before cognitive decline [101,102], neuronal cell loss in the LC is most appreciable in advanced stages of neurodegeneration rather than in the earlier stages (evidence reported from Braak stage III-IV) [31,101,102,129]. Therefore, throughout the pathological course, the volumetric and functional resilience of the LC (including the maintenance of the surrounding LC-peri dendritic and the epi and sub-coeruleus areas [180,181,14]) may provide a supporting and compensating role in the face of the beta-amyloid pathology occurring in the cortex [101,102,180,190,21,17,16]. Interestingly in this regard, a recent work by Bachman et al [174] found positive relationships between the volume of the LC and surface measures in cortical regions including the rostral medial frontal cortex, which has a high density of noradrenergic varicosities [175].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations